Críticas a la religión como categoría universal - Lorca, Martin Becker (Revista cultura y religión, 2023)
Based on a genealogical and conceptual analysis proper to the philosophy of religion, which seeks precisely to problematize the basic categories assumed by religious studies, this article examines two critiques of the concept of religion. The first seeks to de-naturalize this category, illuminating the construction that researchers themselves make of what they study. Insofar as this construction is made possible by the historical conditions of modernity, I affirm the thesis that the category of religion has a modern origin. This implies, in turn, that religion and secularization are born at the same time. The second criticism points to a possible epistemological violence that occurs when projecting the category of religion to non-Western territories, where this split between the religious and the secular, typical of modern European history, has not occurred. The aim of this article is to question the supposed certainty of considering religion as an anthropological constant, without falling, however, into a type of criticism that tends to make the criticized object disappear. I postulate that it is by accepting -rather than canceling- the uncertainty of the concept of religion the way that can give vitality to Religious Studies in Latin America.